LAW ENFORCEMENT AGAINST HUMAN TRAFFICKING IN THE POLICE JURISDICTION AT SANGIHE ISLANDS RESORT - Anriz, Revianto; Prawesthi, Wahyu; Amiq, Bahrul (YURIS: Journal of Court and Justice, 2023)
The form of application is based on mistakes that are in accordance with legal elements and there is no reason for unlawful elimination, the element of intent by the perpetrator (dolus) so that there is no justification or reason for him/her to avoid punishment. Law enforcement efforts in the eradication of human trafficking are implemented through non-penal and penal approaches. Non-penal approaches are conducted through counseling, social education in order to develop the social responsibility of citizens who are aware of human trafficking crimes, legal counseling, resocialization, workshops, etc., especially in crime-prone environments. The penal approach is carried out through legal efforts so that perpetrators of human trafficking crimes are legally processed based on the provisions of laws and regulations up to the court level and execution in order to obtain criminal sanctions and guarantee legal certainty in society. The objective of this research is to analyze the application of criminal sanctions and law enforcement against human traffickers in the Police jurisdiction, North Sulawesi Regional District, Sangihe Islands Resort. This research used a case approach which aims to examine the application of legal norms or rules in legal practice. In addition, legislation is conducted by reviewing all laws and regulations that are related to the legal issues being addressed. The 1945 Constitution of the Republic Indonesia in one of its articles, Article 3, mentions the right not to be enslaved. Therefore, to realize the protection of this right, the Indonesian government needs to regulate human trafficking crimes separately.